2006
DOI: 10.1186/1471-2458-6-295
|View full text |Cite
|
Sign up to set email alerts
|

Irregular breakfast eating and health status among adolescents in Taiwan

Abstract: Background: Regular breakfast eating (RBE) is an important contributor to a healthy lifestyle and health status. The aims of the present study were to evaluate the relationships among irregular breakfast eating (IRBE), health status, and health promoting behavior (HPB) for Taiwanese adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
53
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 29 publications
4
53
1
3
Order By: Relevance
“…In Hong Kong, approximately 10% of school aged children and adolescents were reported to skip their breakfast at least 4 times a week (5), while in Malaysia, it has been found that breakfast is the most frequently missed meal (4). Similar condition was also found in Taiwan, approximately 23.6% participants in their study reported that they ate breakfast irregularly on the schooldays (6). In Indonesia, nearly half of the children population (44.6%) still has breakfast with low nutritional quality (15).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…In Hong Kong, approximately 10% of school aged children and adolescents were reported to skip their breakfast at least 4 times a week (5), while in Malaysia, it has been found that breakfast is the most frequently missed meal (4). Similar condition was also found in Taiwan, approximately 23.6% participants in their study reported that they ate breakfast irregularly on the schooldays (6). In Indonesia, nearly half of the children population (44.6%) still has breakfast with low nutritional quality (15).…”
Section: Introductionsupporting
confidence: 60%
“…Another supporting study from Malaysia found out that infrequent breakfast consumption is associated with higher body adiposity and abdominal obesity as well as higher BMI level in comparison with its counterpart (32) while in Taiwan, it is indicated that adolescents with regular breakfast consumption had a lower risk of being overweight. In the same study, it was also reported that the odds of being overweight for irregular breakfast eating is 51% higher than having breakfast regularly even after controlling demographical variables (6).…”
Section: Introductionmentioning
confidence: 88%
“…While Preziosi et al (12) defined breakfast as the first eating occasion involving a solid food or a beverage that occurred after waking and Yang et al (13) referred to it as food eaten before 09.00 hours irrespective of the meal content, Timlin and Pereira (14) defined it as:…”
Section: Discussionmentioning
confidence: 99%
“…Most breakfast-related studies in the literature have focused on the frequency of breakfast consumption and individuals have been classified into categories such as breakfast skippers, occasional breakfast eaters, frequent breakfast eaters, irregular breakfast eaters and regular breakfast eaters (12,13) . The findings of the present study, which examined breakfast skipping and nutrient adequacy of the breakfast meal, seem to suggest that individuals may not report skipping breakfast per se but the breakfast meal consumed has deficits with respect to energy and several other macro-and micronutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Sebagian besar orangtua maupun guru cenderung menganggap sarapan sebagai prasyarat keberhasilan proses belajar selepas periode puasa yang cukup panjang pada malam sebelumnya. [1][2][3][4] Berdasarkan Riset Kesehatan Dasar 2010, 16,9%-50% anak usia sekolah dan remaja, serta rata-rata 31,2% orang dewasa di Indonesia tidak biasa sarapan. Anak sekolah sekedar mengonsumsi minuman saat sarapan (26,1%), seperti air putih, susu, atau teh dan 44,6% mengonsumsi sarapan berkualitas rendah.…”
unclassified